Chitosan‐based self‐assembled nanomaterials: Their application in drug delivery. Issue 1 (22nd October 2020) - Liu, Ya; Sun, Mengjie; Wang, Ting; Chen, Xiguang; Wang, Hao
Abstract: Nanoparticles have long been one of the most popular delivery systems for enhancing the stability of therapeutic agents, providing targeted drug transportation, sustaining drug concentration at sites of action, and promoting therapeutic efficacy. Chitosan‐based nanoparticles have been widely explored as drug delivery systems due to the unique biological properties, such as easy to chemical modifications, biocompatibility, mucoadhesive feature, and absorption enhancement. In this review, we outline the biological properties and stimuli‐sensitive strategies of chitosan‐based self‐assembled nanoparticles as well as the recent developments in various applications in drug delivery, including cancer treatment, oral administration, skin regeneration, nasal/ocular mucosal administration, and pulmonary drug delivery. Chitosan‐based nanoparticles exhibit excellent features as drug delivery systems due to the outstanding biological properties. As the suitable vehicles for drug administration, chitosan‐based nanoparticles facilitate and improve drug bioavailability in all cases. Abstract : Chitosan‐based nanosystems have been widely explored as delivery vehicles due to their unique biological properties of favorable hemocompatibility, low cytotoxicity, antibacterial activity, and easily controlled drug release profiles. Chitosan nanosystems are suitable to deliver drugs via multiple routes, such as intravenous, oral, ocular, nasal, pulmonary, and transdermal, demonstrating enormous potential in cancer treatment, skin regeneration, tissue engineering, gene therapy, or other fields.